Circuit-averaged modeling of non-ideal low-power DC-AC inverters - Ghizzawi, Farouk (2020)
With the growing demand for electrical DC storage and sources, DC-AC conversion has become an indispensable component for not only high and medium, but also low-power applications. This paper introduces an efficient and accurate multi-harmonic circuit-averaged modeling technique for nonideal pulse-width modulated DC-AC inverters for low-power applications. The proposed model significantly reduces simulation times by using circuit-averaging and accurately anticipates the AC signal response by modeling the circuit behavior at different harmonics. The proposed model deploys the inductor current in the filter at the inverter output as a state variable, and accurately records circuit dynamics while accounting for switching losses associated with non-ideal devices. We show that the developed index-0 and index-1 circuits compare well with transistor-level simulations under a variety of operating conditions.